Integrating virtual worlds with learning management systems : the MULTIS approach - Morgado, Leonel (2017)
Trabalho apresentado em 2016 no 15th International Conference on Ubiquitous Computing and Communications and 2016 8th International Symposium on Cyberspace and Security - IUCC-CSS,Granada, Spain, 2016.